Role of Medial Prefrontal Cortex Serotonin 2A Receptors in the Control of Retrieval of Recognition Memory in Rats - Bekinschtein, Pedro Alejandro (2013)
Often, retrieval cues are not uniquely related to one specific memory, which could lead to memory interference. Controlling interference is particularly important during episodic memory retrieval or when remembering specific events in a spatiotemporal context. Despite a clear involvement of prefrontal cortex (PFC) in episodic memory in human studies, information regarding the mechanisms and neurotransmitter systems in PFC involved in memory is scarce. Althoughthe serotoninergic system has been linkedto PFC functionality and modulation, its role in memory processing is poorly understood.We hypothesizedthatthe serotoninergic system in PFC, in particularthe 5-HT2A receptor (5-HT2AR) could have a role in the control of memory retrieval. In this work we used different versions of the object recognition task in rats to study the role of the serotoninergic modulation in the medial PFC (mPFC) in memory retrieval. We found that blockade of 5-HT2AR in mPFC affects retrieval of an object in context memory in a spontaneous novelty preference task, while sparing single-item recognition memory. We also determined that 5-HT2ARs in mPFC are required for hippocampal–mPFC interaction during retrieval of this type of memory, suggesting that the mPFC controls the expression of memory traces stored in the hippocampus biasing retrieval to the most relevant one.